Patterns of Unilateral and Bilateral Projections From Layers 5 and 6 of the Auditory Cortex to the Inferior Colliculus in Mouse - Vaithiyalingam Chandra Sekaran, Nathiya; Deshpande, Meena S.; Ibrahim, Baher A.; Xiao, Gang; Shinagawa, Yoshitaka; Llano, Daniel A. (Frontiers in Systems Neuroscience, 2021)
The auditory cortex sends massive projections to the inferior colliculus, but the organization of this pathway is not yet well understood. Previous work has shown that the corticocollicular projection emanates from both layers 5 and 6 of the auditory cortex and that neurons in these layers have different morphological and physiological properties. It is not yet known in the mouse if both layer 5 and layer 6 project bilaterally, nor is it known if the projection patterns differ based on projection location. Using targeted injections of Fluorogold into either the lateral cortex or dorsal cortex of the inferior colliculus, we quantified retrogradely labeled neurons in both the left and right lemniscal regions of the auditory cortex, as delineated using parvalbumin immunostaining. After dorsal cortex injections, we observed that approximately 18–20% of labeled cells were in layer 6 and that this proportion was similar bilaterally. After lateral cortex injections, only ipsilateral cells were observed in the auditory cortex, and they were found in both layer 5 and layer 6. The ratio of layer 5:layer 6 cells after lateral cortex injection was similar to that seen after dorsal cortex injection. Finally, injections of different tracers were made into the two inferior colliculi, and an average of 15–17% of cells in the auditory cortex were double-labeled, and these proportions were similar in layers 5 and 6. These data suggest that (1) only the dorsal cortex of the inferior colliculus receives bilateral projections from the auditory cortex, (2) both the dorsal and lateral cortex of the inferior colliculus receive similar layer 5 and layer 6 auditory cortical input, and (3) a subpopulation of individual neurons in both layers 5 and 6 branch to innervate both dorsal cortices of the inferior colliculus.